2003
DOI: 10.1159/000071352
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interleukin 1β and Receptor Antagonist Gene Polymorphisms with Primary Open-Angle Glaucoma

Abstract: Purpose: Genetic factors are known to play a role in the etiology of glaucoma. More specifically, the role of the immune system is highly suspected. We evaluated the association between 2 polymorphisms in the interleukin (IL) 1β gene (IL-1 promoter 511, IL-1 exon 5) and 1 polymorphism in the IL-1 gene receptor antagonist (IL-1Ra) intron 2 with primary open-angle glaucoma (POAG). Patients and Methods: Fifty-eight POAG patients and 105 healthy volunteers were enrolled in this study. Analysis based on polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…In our laboratory, we investigated the relations of many polymorphisms with apoptosis, immune and cell morphogenesis. We have already found some single nucleotide polymorphisms (SNPs) associated with POAG [3,4] , and we tried to map POAG with genetic polymorphisms. E-cadherin (E-CDH) is closely related to matrix metalloproteinases (MMPs) involved in the outfl ow of aqueous humor in trabecular meshwok.…”
Section: Introductionmentioning
confidence: 99%
“…In our laboratory, we investigated the relations of many polymorphisms with apoptosis, immune and cell morphogenesis. We have already found some single nucleotide polymorphisms (SNPs) associated with POAG [3,4] , and we tried to map POAG with genetic polymorphisms. E-cadherin (E-CDH) is closely related to matrix metalloproteinases (MMPs) involved in the outfl ow of aqueous humor in trabecular meshwok.…”
Section: Introductionmentioning
confidence: 99%
“…The interleukin-1 gene cluster [37] (including IL-1B) lies approximately 0.5 cM beyond the distal end of the GLC1B haplotype identifi ed in this study. A polymorphism within IL-1B has recently been associated with sporadic POAG in the Chinese population [38] , although investigation of this polymorphism showed no segregation with the POAG phenotype in pedigree GTas15 (data not shown). It is also interesting to note that mer tyrosine kinase protooncogene ( MERTK : MIM# 604705), a gene associated with retinitis pigmentosa [39] (a disease that also results in visual fi eld loss) is located near marker D2S2269 at the distal end of the haplotype of interest.…”
Section: Discussionmentioning
confidence: 94%
“…Our previous studies reported that the IL-1α (-889) T allele polymorphism may be a risk factor in POAG patients but not in NTG patients [22,38] . Lin et al [39] found that the IL-1β (+3953)T allele was significantly more common in POAG patients but not in NTG patients [40] . In future studies, proteomic analyses may be useful for determining the exact roles of cytokines genes in the development of glaucoma.…”
Section: Discussionmentioning
confidence: 99%